Quality of children's menus in malls in Brazil - Janaína Guimarães Venzke; Giulia Antonietti Aranalde; Ana Luiza Sander Scarparo; Ada Rocha (Instituto Materno Infantil de Pernambuco, 2023)
Abstract Objectives: characterize the availability and assess the nutritional quality of children's menus ofered in regular and fast food restaurants in Brazilian malls. Methods: this is an observational and cross-sectional study. Data were collected on the websites of each restaurant and in food sales applications, with a questionnaire consisting of two sections: characterization of the restaurant and characterization of the children's menu. Data collection took place in ten capitals in the fve regions of Brazil. Results: 116 children's menus were evaluated. The study identifed a higher number of regular (n=70, 60%) than fast-food (n=46,40%) restaurants. The cooking methods most used in the main dishes were grilled (n=236, 64%) and boiled (n=74, 20%), and in the side dishes were boiled (n=204, 53%) and fried (n=109, 28%). Only 40% (n=46) of the menus contained vegetables. Less than 10% (n=seven) ofered fruit as dessert, 31% (n = 36) had drinks included in the children's menu and 22% (n=25) ofered gifts associated with the menu. Only 32 (28%) restaurants had the combination of beans and rice. Conclusion: most of the options ofered to children were of low nutritional quality, with low ofer of vegetables, fruits and the traditional beans and rice. The beverages included in the menus, most of them sugary, can contribute to a high-energy intake. There is a need to provide healthy options and encourage these choices.